Effects of partial substitution of NaCl on gel properties of fish myofibrillar protein during heating treatment mediated by microbial transglutaminase. (July 2018) - Feng, Jianhui; Cao, Ailing; Cai, Luyun; Gong, Lingxiao; Wang, Jing; Liu, Yongguo; Zhang, Yuhao; Li, Jianrong
Abstract: The effects of partial substitution of NaCl with KCl, MgCl2 and CaCl2 on gelation properties of myofibrillar protein (MP) mediated by microbial transglutaminase during the heating process were studied, including texture, color, water-holding capacity, rheological properties, Raman spectra and microstructure. Ranking of chlorinated salts efficiency showed NaCl > KCl > MgCl2 > CaCl2 . The NaCl and KCl groups of MP gels exhibited similar water-holding capacity and gel strength. The gel strength was all decreased in the MP gels containing KCl, CaCl2 and MgCl2 compared to the NaCl group, while the KCl group reduced the gel strength to a less extent. The rheological properties of NaCl and KCl groups showed significant higher G′ and G″ values compared to the control group. Thus, the utilization of chlorinated salts substitutes is a promising way to reduce sodium content in fish products. These results could be used for references in developing low-sodium meat and fish products. Highlights: The effects of chlorinated salts on gelation properties were studied. Using KCl resulted in acceptable gel strength and rheological properties. Ranking of chlorinated salts efficiency showed NaCl > KCl > MgCl2 > CaCl2. Partial substitution of NaCl could be an alternative for healthier diet.